Transformasi Digital Public Relations dalam Membangun Citra Organisasi di Era Media Sosial - Randa Satini Ayu; Umar Abdur Rahim; Intan Kemala (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2026)
The development of digital technology has transformed public relations practices from conventional communication models to digital-based communication. Digital Public Relations (Digital PR) enables organizations to build more interactive, rapid, and transparent relationships with their publics through social media, websites, and various digital platforms. This study aims to analyze the role of Digital Public Relations in building organizational image in the social media era. The research employs a literature review method by examining various national journal articles related to Digital PR and Cyber Public Relations. The findings indicate that Digital PR significantly contributes to enhancing organizational image through two-way communication, online reputation management, increased audience engagement, and more effective information dissemination. Social media serves as the primary instrument of Digital PR implementation because it facilitates participatory relationships between organizations and their publics. However, challenges such as digital reputation crises, the spread of negative information, and the demand for rapid responses remain critical issues that must be strategically managed by public relations practitioners. Therefore, effective Digital PR strategies are essential to maintain organizational reputation and strengthen public trust in the digital era.